2013
DOI: 10.1080/00268976.2013.813594
|View full text |Cite
|
Sign up to set email alerts
|

Using collective variables to drive molecular dynamics simulations

Abstract: A software framework is introduced that facilitates the application of biasing algorithms to collective variables of the type commonly employed to drive massively parallel molecular dynamics (MD) simulations. The modular framework that is presented enables one to combine existing collective variables into new ones, and combine any chosen collective variable with available biasing methods. The latter include the classic time-dependent biases referred to as steered MD and targeted MD, the temperature-accelerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
978
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 860 publications
(982 citation statements)
references
References 74 publications
(121 reference statements)
2
978
0
2
Order By: Relevance
“…Within several nanoseconds, the potassium ion bound in site III migrated towards sites I and II. We furthermore used metadynamics simulations (see Experimental procedures) to calculate potential of mean force (PMF) along two collective variables (23) characterizing the bound ion density; the results revealed that protonation of D926 leads to a more favorable binding of K + to binding sites I and II and not to site III ( Figure 1E). Occupation of site III by Na + ions, on the other hand, is consistent with the presence of such a cation in the crystal structure, thus leading us to conclude that D926 should be deprotonated in the Na + -bound E1P state, but not in the K + -bound E2P state.…”
Section: Resultsmentioning
confidence: 99%
“…Within several nanoseconds, the potassium ion bound in site III migrated towards sites I and II. We furthermore used metadynamics simulations (see Experimental procedures) to calculate potential of mean force (PMF) along two collective variables (23) characterizing the bound ion density; the results revealed that protonation of D926 leads to a more favorable binding of K + to binding sites I and II and not to site III ( Figure 1E). Occupation of site III by Na + ions, on the other hand, is consistent with the presence of such a cation in the crystal structure, thus leading us to conclude that D926 should be deprotonated in the Na + -bound E1P state, but not in the K + -bound E2P state.…”
Section: Resultsmentioning
confidence: 99%
“…This can be done during post processing on the trajectory file, much like a conventional analysis tool, or on-the-fly during the simulation. Other software is available for analyzing existing trajectories [7,20,21,22,23,24] or for biasing MD simulations [15,9,25,26,27,7,6]. PLUMED 2, however, is the only code we know of that allows users to do both sets of tasks with a single syntax.…”
Section: Plumed 2 Overviewmentioning
confidence: 99%
“…Furthermore, given that the interface with the complex MD code was looked after deep within PLUMED and that the coding style of PLUMED was both simple and flexible, it was hoped that developers would use the code to share their methods with the widest possible community. PLUMED has been rather successful in both respects and the plug-in model has been adopted by other researchers [15]. To date there have been approximately 3200 downloads of PLUMED from our website, more than 150 articles in which the original PLUMED article has been cited, more than 200 users who have subscribed to our mailing list, and 20 different super users who have contributed code fragments to our repository.…”
Section: Introductionmentioning
confidence: 99%
“…We verified that without this repulsive wall the overlaps occur rarely and only in the last windows of the FEP decoupling procedure; the effect on the estimated free energy is generally comparable to the statistical error. The harmonic restraint as well as the repulsive wall were implemented using the Collective Variables Module available in NAMD 73 .…”
Section: Free Energy Calculationsmentioning
confidence: 99%